Development and Utilization Webquest as an Instructional Strategy in Teaching Thermodynamics in Colleges of Education in Kwara State - Olanrewaju Yetunde Beatrice (Journal of Educational Sciences, 2023)
The worldwide education system has been significantly impacted by the growth of technology. The purpose of the study was to developed and utilized Webquest instructional package for the teaching of thermodynamic in chemistry. This intended to see if its usage will bring significance understanding to pre service chemistry teacher’s performance Thermodynamics is one of the chemistry topics students find difficult to understand. The study was carried out in colleges of education in Kwara State. All third-year chemistry students at the colleges of education made up the study's population. A thermodynamics performance test in Chemistry and the Webquest software program served as the study's two research tools. Data for the pre-test and post-test were collected at the start and conclusion of the study, respectively. The study revealed that students had a different impression of studying thermodynamics, in accordance with the research aims and findings. The students in the webQuest group claimed that using the webQuest package gave them a fresh perspective on how to comprehend the notion of thermodynamics, it is essential for the organizations in charge of teacher training colleges across the nation to promote the use of webQuest in instruction and training for teachers-in-training.